2010
DOI: 10.1007/s11606-010-1313-1
|View full text |Cite
|
Sign up to set email alerts
|

Dependence on Emergency Care among Young Adults in the United States

Abstract: BACKGROUND: Young adults have a high prevalence of many preventable diseases and frequently lack a usual source of ambulatory care, yet little is known about their use of the emergency department. OBJECTIVE: To characterize care provided to young adults in the emergency department. DESIGN, SETTING, AND PARTICIPANTS: Cross-sectional analysis of visits from young adults age 20 to 29 presenting to emergency departments (N=17,048) and outpatient departments (N=14,443) in the National Hospital Ambulatory Medical Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 20 publications
5
63
2
Order By: Relevance
“…18,19 Furthermore, the results also indicate that younger patients may be more likely to rely on the ED for their health care than do older patients, which is a phenomenon that an earlier study has suggested. 20 This phenomenon may be a result of younger patients' unmet needs owing to insufficient health insurance coverage or inexperience in navigating through the health care system.…”
Section: Original Research and Contributionsmentioning
confidence: 99%
“…18,19 Furthermore, the results also indicate that younger patients may be more likely to rely on the ED for their health care than do older patients, which is a phenomenon that an earlier study has suggested. 20 This phenomenon may be a result of younger patients' unmet needs owing to insufficient health insurance coverage or inexperience in navigating through the health care system.…”
Section: Original Research and Contributionsmentioning
confidence: 99%
“…We evaluated adolescents between 15 and 19 years of age and defined young adults as those between 20 and 29 years of age on the basis of previous studies. 22,23 …”
Section: Study Time Period and Age Groupsmentioning
confidence: 99%
“…Young adults have traditionally been less integrated into the healthcare system, as they are more likely to be uninsured and less likely to have a usual source of care. [7][8][9] Provider specialty and both provider and patient perceptions of risk based on patient age, gender, race/ethnicity, or comorbidities may impact awareness and treatment as well. A recent study of adults with regularly scheduled physician visits who met clinical criteria for hypertension found that those who were ages 18-24 years vs. at least 60 years of age were 28 % less likely to have their hypertension diagnosed by their physician.…”
Section: Introductionmentioning
confidence: 99%